STRUCTURAL AND LEXICAL AMBIGUITY IN THE POLITICAL ARTICLE OF JAKARTA POST - Rika Imadawati Purba; Nenni Triana Sinaga; Kammer Tuahman Sipayung (J-Shelves of Indragiri (JSI), 2023)
This research aims to analyze the structural and lexical ambiguity in the political article in the Jakarta Post. A qualitative analysis method was used in this study. The observation was done by collecting political articles from the Jakarta Post online. Interactive models were employed with three steps: data condensation, data display, and drawing concluding/verifying. The findings show many structural and lexical ambiguity cases in political articles of the Jakarta Post, which can lead to misunderstandings and wrong interpretations. 57 structural ambiguities and 63 lexical ambiguities were found in ten political articles. The accuracy in choosing words and using word structure impacts writing quality. The writing quality helps the readers understand the information in political articles.